DM intake by feedlot beef cattle: factors that impact intake patterns - Silvestre, A. M. [UNESP]; Cruz, G. D.; Owens, F. N.; Pereira, M. C.S.; Hicks, R. B.; Millen, D. D. [UNESP] (Elsevier, 2023)
DM intake (DMI) for individual pens of cattle is recorded daily or averaged across each week by most commercial feedlots as an index of performance. Numerous factors impact DMI by feedlot cattle. Some are available at the start of the feedlot period (initial BW, sex), and others become available early in the feeding period (daily DMI during adaptation) or more continuously (daily DMI from the previous week). To evaluate the relative impact of these factors on daily DMI during individual weeks within the feedlot period, we employed a dataset compiled from 2009 to 2014 from one commercial feedlot, including 4 132 pens (485 458 cattle), which were split into two fractions: 80% were used to calculate DMI regressions on these factors to develop a prediction equation for mean DMI for each week of the feeding period, and 20% were reserved to test the adequacy of these prediction equations. Correlations were used to determine the relationship between all available variables with observed DMI. These variables were then included in the generalized least squares regression models. A veracity test of the model was performed against the reserved data. Daily DMI from previous week was the factor most highly correlated with daily DMI (P < 0.10) during from week 6 to week 31, accounting for approximately 70% of the variation, followed by mean daily DMI during adaptation period (weeks 1–4), including in the prediction model from weeks 5 to 12. Initial shrunk BW (ISBW) was the third most correlated factor, which was included in prediction equations from week 5 to week 20. Sex entered the prediction model only after week 8. Daily DMI for each test week within the feeding period was predicted closely (r2 = 0.98) by these four factors (RMSE = 0.155 kg). In conclusion, the mean daily DMI during each week of the finishing period for a pen of cattle could be predicted closely based on mean daily DMI intake during the previous week plus other variables available early in a feedlot period (daily DMI during adaptation period, ISBW and sex).
Keywords: Management; Model; Prediction; Sex; Week